The bone-preserving effects of exendin-4 in ovariectomized rats - Sun, Han-xiao; Lu, Nan; Liu, Dong-mei; Zhao, Lin; Sun, Li-hao; Zhao, Hong-yan; Liu, Jian-min; Tao, Bei (Endocrine, 2016)
Exendin-4 was found to be beneficial to the skeleton in diabetic rodents. In this study, we assessed the changes of bone mineral densities (BMDs) and quality in non-diabetic ovariectomized (OVX) rats after treatment with exendin-4. The regulatory role of exendin-4 on osteoblastogenesis and adipogenesis in rat bone marrow stromal cells (BMSCs) was also explored. Three months after sham surgery or OVX, 18 5-month-old female Wistar rats were divided into three groups and received the following treatment for 8 weeks: (1) Sham + vehicle; (2) OVX + vehicle; and (3) OVX + exendin-4 20 µg/kg/day. Micro-CT and three-point bending test were used to evaluate the BMDs, bone morphometric parameters, and biomechanical properties. Real-time PCR and Western blot were performed to measure gene and protein expression after exendin-4 treatment in adipogenesis and osteoblastogenesis of rat BMSCs. Exendin-4 could improve trabecular volume, thickness, and number, increase BMD, and reduce trabecular spacing in the lumbar spine and femur of OVX rats. Exendin-4 had little impact on the mechanical resistance of femurs to fracture. When rat BMSCs were treated with exendin-4, the mRNA expression levels of runt-related transcription factor 2 (Runx2), alkaline phosphatase (ALP), and collagen α1 (Coll-1) were increased, while those of peroxisome proliferators activated receptor γ (PPARγ) and CCAAT/enhancer-binding protein (C/EBPα) decreased. Exendin-4 treatment also resulted in increased expression levels of p38, p42/44, and β-catenin proteins. Exendin-4 was anabolic to bone in OVX rats possibly by facilitating osteoblastogenesis while repressing adipogenesis during BMSC lineage differentiation.